A modified DNA barcode approach to define trophic interactions between native and exotic pentatomids and their parasitoids. Issue 2 (10th October 2018) - Gariepy, Tara D.; Bruin, Allison; Konopka, Joanna; Scott‐Dupree, Cynthia; Fraser, Hannah; Bon, Marie‐Claude; Talamas, Elijah
Abstract: The establishment of invasive Halyomorpha halys (Stål) outside of its native range may impact native species assemblages, including other pentatomids and their scelionid parasitoids. This has generated interest in defining species diversity and host‐parasitoid associations in this system to better understand the impact of invasive alien species on trophic interactions in invaded regions. Information on scelionid–pentatomid associations in natural habitats is lacking, and species‐level identification of these associations can be tenuous using rearing and dissection techniques. Naturally occurring pentatomid eggs were collected in areas where H. halys has established in Canada and were analysed using a modified DNA barcoding approach to define species‐level trophic interactions. Identification was possible for >90% of egg masses. Eleven pentatomid and five scelionid species were identified, and trophic links were established. Approximately 70% of egg masses were parasitized; parasitism and parasitoid species composition were described for each species. Telenomus podisi Ashmead was the dominant parasitoid and was detected in all host species. Trissolcus euschisti Ashmead was detected in several host species, but was significantly more prevalent in Chinavia hilaris (Say) and Brochymena quadripustulata (Fabricius). Trissolcus brochymenae Ashmead and Tr. thyantae Ashmead were recorded sporadically. Parasitism of H. halys was 55%, and this species was significantly less likely to be parasitized than native pentatomids. The scelionid species composition of H. halys consisted of Te. podisi, Tr. euschisti and Tr. thyantae . Although these species cannot develop in fresh H. halys eggs, we demonstrate that parasitoids attempt to exploit this host under field conditions.